2018
DOI: 10.4103/ijmbs.ijmbs_73_17
|View full text |Cite
|
Sign up to set email alerts
|

Rate, Timing, and Severity of hypoglycemia in adolescents with Type 1 diabetes during ramadan fasting: A study with freestyle libre flash glucose monitoring system

Abstract: Objectives: The objective of this study is to assess the frequency, timing, and severity of hypoglycemia in adolescents with type 1 diabetes mellitus (T1DM) during fasting the month of Ramadan. Patients and Methods: Twenty-five adolescents with T1DM who fasted Ramadan were monitored using the FreeStyle Libre ® flash glucose monitoring (FGM) system. Percentage and total duration of hypoglycemia were extracted from the FGM downloads, and the differences were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The length of fasting duration during Ramadan is another variable that impacted the occurrence of hypoglycemia and HE among fasting patients with diabetes during Ramadan. This is supported by repeated reports that most HE occurred in the daytime hours before iftar (sunset “breakfast” meal) among patients with diabetes observing Ramadan fasting ( 8 , 45 , 49 , 51 , 54 , 61 , 71 , 102 104 ).…”
Section: Discussionsupporting
confidence: 64%
“…The length of fasting duration during Ramadan is another variable that impacted the occurrence of hypoglycemia and HE among fasting patients with diabetes during Ramadan. This is supported by repeated reports that most HE occurred in the daytime hours before iftar (sunset “breakfast” meal) among patients with diabetes observing Ramadan fasting ( 8 , 45 , 49 , 51 , 54 , 61 , 71 , 102 104 ).…”
Section: Discussionsupporting
confidence: 64%
“…[16] Besides improvement of glycemic control, in Ramadan Fasting, the use of technologically-advanced diabetes control technologies is demonstrated to be of great benefit in prediction of hypoglycemia and glycemic excursions. [17][18][19] Several studies have highlighted the advantages of other advanced technologies such as flash glucose monitoring (FGM) systems in fasting patients with T1DM [20].…”
Section: Management Of Patients With Type 1 Diabetesmentioning
confidence: 99%
“…Data from CGM downloads have indicated increased risks of hypoglycaemia among young people with diabetes who fast during Ramadan, especially during daylight hours. 59 ISPAD guidelines for young people with T1DM provide guidance on the use of CGM and isCGM during Ramadan fasting, 60 and ASPED has recently published recommendations for the use of CGM in the Middle East and North Africa region which include advice for managing glucose levels in Ramadan. 61 Furthermore, several studies have demonstrated that CGM with trend arrows can help adults and children to fast without the risk of life-threatening episodes of severe hypoglycaemia or diabetic ketoacidosis (DKA), provided that they are well trained on the use of the technology.…”
Section: Ramadanmentioning
confidence: 99%